Analyzing the Relationship Among Unemployment, Income, Population, and Crime Rates: The Case of Turkiye - Şerife Merve Koşaroğlu (Sosyal Siyaset Konferansları Dergisi)
Unemployment is the primary economic problem to be solved. Unlike other macroeconomic indicators, the effects of unemployment can be prolonged and serious. Besides its economic cost, unemployment can also increase the severity of the outcomes because it results in social and psychological consequences. Combating unemployment contributes to economic growth and development. Studying unemployment, income, and crime relationships makes it possible to evaluate a variety of costs of unemployment. Our study aims to evaluate these costs, the relationship among unemployment, income, crime, and population growth from 1990 to 2019 was analyzed. The results of cointegration tests show that there is a long-term relationship among unemployment, income, population growth, and crime in Turkiye. According to the results obtained from the causality test, there is a one-way causality relationship between the crime rates and unemployment variables. There is a twoway causality relationship between crime rates and population growth. It has been determined that there is a one-way causality relationship between the income and unemployment variables and the population growth variable. Because unemployment is a chronic problem in Turkiye, it is clear that its effects create more serious conditions in the economy. Taking this reality into consideration while deciding on the economic policies and fighting unemployment could have a supportive effect over economic and social development.